Probabilidades de empleo-desempleo en Medellín: evidencia empírica para pensar un seguro de desempleo en Colombia (2013)
ABSTRACT: To estimate the employment and unemployment probability of the labor force in the metropolitan area of Medellín (Colombia), and to analyze the duration of the unemployment period experienced by a group of unemployed workers in Medellín during 2004 in terms of individual characteristics and job search time. Methodology: a crosssectional, descriptive study using secondary and primary sources. Two central analysis categories were defined for the study: employed labor force and unemployed labor force. Likewise, logistic regression and nonparametric estimation techniques such as the Kaplan-Meier survival tables were applied. Results: unemployed women aged 44 and older, with secondary education and work experience in the industry and commerce sectors were the most likely to remain unemployed, and therefore spend more time searching for a job. Discussion: the main findings of this study and their relationship with other local and national studies demonstrate that the duration of the unemployment periods in Colombia is, in most cases, long; therefore, this factor should be taken into account while discussing the scope and nature of unemployment insurance plans.